2017
DOI: 10.1136/bmjopen-2016-015260
|View full text |Cite
|
Sign up to set email alerts
|

Childhood hospitalisation and related deaths in Hanoi, Vietnam: a tertiary hospital database analysis from 2007 to 2014

Abstract: ObjectiveTo describe hospital admission and emergency visit rates and potential risk factors of prolonged hospitalisation and death among children in Hanoi.Study designA retrospective study reviewed 212 216 hospitalisation records of children (aged 0–17) who attended the Vietnam National Children's Hospital in Hanoi between 2007 and 2014. Four indicators were analysed and reported: (1) rate of emergency hospital visits, (2) rate of hospitalisation, (3) length of hospital stay and (4) number of deaths. The risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
2
10
1
Order By: Relevance
“…In Vietnam, respiratory diseases, bacterial and parasitic infections accounted for most hospital admissions in children 25. Compared with the our observed hospitalisation rate of 14.8% for all causes during the first 6 months, a previous cohort study with 6 months follow-up found 8.8% and 4% of infants required inpatient admission for suspected pneumonia and diarrhoeal illness, respectively 13.…”
Section: Discussioncontrasting
confidence: 73%
“…In Vietnam, respiratory diseases, bacterial and parasitic infections accounted for most hospital admissions in children 25. Compared with the our observed hospitalisation rate of 14.8% for all causes during the first 6 months, a previous cohort study with 6 months follow-up found 8.8% and 4% of infants required inpatient admission for suspected pneumonia and diarrhoeal illness, respectively 13.…”
Section: Discussioncontrasting
confidence: 73%
“…An estimated 6.2 million children under the age of 15 died in 2018, mostly from preventable causes, and most of whom lived in middle- and low-income countries [ 1 ]. In Vietnam, an 8-year retrospective study (2007–2014) among 212,216 hospitalised children under the age of 17 in Hanoi [ 17 ] showed that ID was responsible for the majority hospitalisations with RTIs accounting for 37.7% of cases, other bacterial and parasitic infections for 19.8%, and gastrointestinal disorders for 10.2%.…”
Section: Discussionmentioning
confidence: 99%
“…The overall hospital mortality rate was lower than reported in other Vietnamese studies. A retrospective survey of 12,389 paediatric emergency visits showed that mortality was 1.1% [ 17 ]. An 8.6% mortality rate was reported in neonates [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The overall hospital mortality rate was lower than reported in other Vietnamese studies. A retrospective survey of 12,389 paediatric emergency visits showed that mortality was 1.1% [16].…”
mentioning
confidence: 99%